Ankle Intrinsic Stiffness in Subcortical Poststroke Subjects. Issue 3 (4th May 2017) - Sousa, Andreia S. P.; Santos, Rubim; Silva, Augusta
ABSTRACT: The authors' purpose was to evaluate bilateral ankle intrinsic stiffness in subcortical poststroke subjects. Ten subcortical poststroke subjects and 10 healthy controls participated in this study. The ankle passive stiffness at 3 different speeds and the electromyographic activity of the soleus, the gastrocnemius, and the tibialis anterior muscles of poststroke contralesional (CONTRA) and ipsilesional (IPSI) limbs and of one limb of healthy subjects were assessed. Ankle electromyographic activity was collected to ensure that reflexive or voluntary muscle activity was not being elicited during the passive movements. A significant interaction was observed between the effects of the limb (IPSI vs. CONTRA vs. control) and ankle position, F (4, 28) = 3.285, p = .025, and between the effects of the limb and the velocity of stretch, F (2, 14) = 4.209, p = .037. While increased intrinsic stiffness was observed in the CONTRA limb of poststroke subjects at ankle neutral position when the passive stretch was applied with a velocity of 1°/s ( p = .021), the IPSI limb of poststroke subjects presented increased stiffness at 20º of plantar flexion when the stretch was applied with a velocity of 5°/s ( p = .009) when compared to healthy group. Subcortical poststroke subjects present increased intrinsic stiffness in both the CONTRA and IPSI limbs in specific ankle amplitudes.